PUNAHNYA ETIKA MORAL ELIT POLITIK DI INDONESIA - jurnalmap map; Putu Ari Saruhum Hasibuan; Mei Indrawati; Cathrine Sri Hartati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
ABSTRACT The problem of corruption has reached its peak, the establishment of institutions that handle this case has carried out its functions well but the trend of corruption cases does not decrease every day but instead jumps sharply. vision, mission, goals become measurable and directed, political parties have a reconciliation process that can produce good politicians who are able to make political decisions or actions. The political elite prioritizes public interests and ethics. done and the corruption gap is closed. Keywords: moral ethics, responsibility, political elite